Symposium on Resource Rich Economies: Introduction. - van der Ploeg, F; Venables, T (Oxford University Press, 2009)
The papers in this symposium are a selection of those presented at the first annual conference of the Oxford Centre for the Analysis of Resource Rich Economies (Oxcarre) held in December 2007. Countries rich in natural resources have had diverse economic experiences, with some using resources to achieve rapid economic growth, and others experiencing a resource ‘curse’. The objectives of the conference, and of Oxcarre, are to develop research into the particular economic issues faced by resource rich economies, to inform policy design in these countries, and to bring together experts in this field from around the world.